Repair of DNA Alkylation Damage by the Escherichia coli Adaptive Response Protein AlkB as Studied by ESI-TOF Mass Spectrometry - Li, Deyu; Delaney, James C.; Page, Charlotte M.; Chen, Alvin S.; Wong, Cintyu; Drennan, Catherine L.; Essigmann, John M. (Journal of Nucleic Acids, 2010)
DNA alkylation can cause mutations, epigenetic changes, and even cell death. All living organisms have evolved enzymatic and non-enzymatic strategies for repairing such alkylation damage. AlkB, one of the Escherichia coli adaptive response proteins, uses an α-ketoglutarate/Fe(II)-dependent mechanism that, by chemical oxidation, removes a variety of alkyl lesions from DNA, thus affording protection of the genome against alkylation. In an effort to understand the range of acceptable substrates for AlkB, the enzyme was incubated with chemically synthesized oligonucleotides containing alkyl lesions, and the reaction products were analyzed by electrospray ionization time-of-flight (ESI-TOF) mass spectrometry. Consistent with the literature, but studied comparatively here for the first time, it was found that 1-methyladenine, 1,N 6-ethenoadenine, 3-methylcytosine, and 3-ethylcytosine were completely transformed by AlkB, while 1-methylguanine and 3-methylthymine were partially repaired. The repair intermediates (epoxide and possibly glycol) of 3,N 4-ethenocytosine are reported for the first time. It is also demonstrated that O 6-methylguanine and 5-methylcytosine are refractory to AlkB, lending support to the hypothesis that AlkB repairs only alkyl lesions attached to the nitrogen atoms of the nucleobase. ESI-TOF mass spectrometry is shown to be a sensitive and efficient tool for probing the comparative substrate specificities of DNA repair proteins in vitro.